Islamic Bank Financing and It’s Impact on Small Medium Enterprise’s Performance - Faisol Faisol (ETIKONOMI, 2017)
The purpose of this paper is to examine the influence of Islamic bank’s financing toward the business performance. Besides that, this paper is going to analyze how far the influence of Islamic bank financing toward Small Medium Enterprises (SME’s) welfare. This research is using partial least square analysis. The population of this research is all of the small medium enterprises especially farmers and industries in the District of Kediri who got Islamic bank financing for one year. The results showed that the Islamic bank financing has significant influence with a positive direction on the SMEs’s performances. This means that when the Islamic bank financing improved, will improve the SMEs’s performance. Further Islamic bank financing has a significant effect with positive direction towards the SMEs’s Welfare.DOI: 10.15408/etk.v16i1.4404